Adapting Physiology in Functional Human Islet Organogenesis - Yoshihara, Eiji (Frontiers in Cell and Developmental Biology, 2022)
Generation of three-dimensional (3D) structured functional human islets is expected to be an alternative cell source for cadaveric human islet transplantation for the treatment of insulin-dependent diabetes. Human pluripotent stem cells (hPSCs), such as embryonic stem cells (hESCs) and induced pluripotent stem cells (hiPSCs), offer infinite resources for newly synthesized human islets. Recent advancements in hPSCs technology have enabled direct differentiation to human islet-like clusters, which can sense glucose and secrete insulin, and those islet clusters can ameliorate diabetes when it’s transplanted into rodents or non-human primates (NHP). However, the generated hPSCs-derived human islet-like clusters are functionally immature compared with primary human islets. There remains a challenge to establish a technology to create fully functional human islets in vitro, which are functionally and transcriptionally indistinguishable with cadaveric human islets. Understanding the complex differentiation and maturation pathway is necessary to generate fully functional human islets for a tremendous supply of high-quality human islets with less batch-to-batch difference to millions of patients. In this review, I summarized the current progress in the generation of 3D structured human islets from pluripotent stem cells and discussed the importance of adapting physiology for in vitro functional human islet organogenesis and possible improvements with environmental cues.